The corporate purchase of property insurance: Chinese evidence - Zou, Hong; Adams, Mike B. (Journal of Financial Intermediation, 2006)
Using a panel data set (1997–1999) for 235 publicly listed companies in the People's Republic of China (PRC), this study tests empirically whether the purchase of property insurance mitigates principal-agent (agency) incentive conflicts. In contrast to prior studies, we first estimate a probit insurance participation decision model and then a fixed-effects insurance volume decision model (with Heckman's sample selection correction) in order to shed light on the determinants of both property insurance participation and volume decisions. Our results suggest that a major motivation for the corporate purchase of insurance in China appears to be the mitigation of agency conflicts. Additionally, various ownerships seem to have different impacts on the corporate purchase of insurance in China. Moreover, the results show that the same factor can have different impacts on the insurance participation and volume decisions, and that binding financial conditions may be a key factor accounting for such observed differences.